1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00063.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of His113 and His114 in Pyruvate Decarboxylase from Zymomonas Mobilis

Abstract: Pyruvate decarboxylase (PDC) is one of several enzymes that require thiamin diphosphate (ThDP) and a divalent cation as essential cofactors. Recently, the three-dimensional structures of the enzyme from two yeasts have been determined. While these structures shed light on the binding of the cofactors and the reaction mechanism, the interactions between the substrate pyruvate and the enzyme remain unclear. We have used PDC from Zynzomonas mobilis as a model for these enzymes in order to study substrate binding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 53 publications
2
67
0
Order By: Relevance
“…The effect of pH on k cat /K m compared to k cat has been well documented for this enzyme by titration curves, with pK a values estimated at 6.23 to 6.45 for the residue involved in modulating substrate binding (21,43). The deprotonation of His113 has been suggested to lead to conformational changes that result in a flexible loop (residues 105 to 112) to close over the active site during catalysis (43). Both His113 and His114 are conserved in all PDC proteins that have been characterized.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of pH on k cat /K m compared to k cat has been well documented for this enzyme by titration curves, with pK a values estimated at 6.23 to 6.45 for the residue involved in modulating substrate binding (21,43). The deprotonation of His113 has been suggested to lead to conformational changes that result in a flexible loop (residues 105 to 112) to close over the active site during catalysis (43). Both His113 and His114 are conserved in all PDC proteins that have been characterized.…”
Section: Resultsmentioning
confidence: 99%
“…First and foremost, the active site as such is complete only in the activated state. A vital role has been ascribed to His-113 in ZmPDC, as part of a catalytic dyad supporting aldehyde release (44,50). Its position is equivalent to that of His-114 in ScPDC and KlPDC, respectively, which reorients upon activation.…”
Section: Structural Implicationsmentioning
confidence: 99%
“…It is proposed that this hydrogen bond promotes the generation of a resonance form with a positively charged imino-group at the 4 H -position of the pyrimidine ring. The side chain of His481 is close to this charged imino group and it has been suggested that His481 (which corresponds to His113 or His114 in Zymomonas mobilis PDC which have been shown to be involved in various aspects of PDC function [19,139]) may abstract the proton from the imino group, which would increase the pK a of the imino group su ciently that it could in turn remove the proton from the C2 of the thiazolium ring. One problem of this mechanism is that in mammalian TKs His481 is replaced by a glutamine [138], rendering the proposed catalytic function of His481 questionable.…”
Section: Catalytic Mechanism Of Tkmentioning
confidence: 99%